2016
DOI: 10.1371/journal.pone.0165037
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes in Science Education Resources: A Visual Content Analysis

Abstract: More men are studying and working in science fields than women. This could be an effect of the prevalence of gender stereotypes (e.g., science is for men, not for women). Aside from the media and people’s social lives, such stereotypes can also occur in education. Ways in which stereotypes are visible in education include the use of gender-biased visuals, language, teaching methods, and teachers’ attitudes. The goal of this study was to determine whether science education resources for primary school contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 37 publications
4
55
0
9
Order By: Relevance
“…Well-known issues such as familial obligation and childbirth have been identified as constraints on women's participation in science, but increasingly research is revealing the subtle and invisible ways in which scientific cultures privilege certain perspectives, bodies, and backgrounds and devalue others (Jarreau 2016;Skibba 2016;Cheryan et al 2017;Nelson 2017;Rosen 2017). Studies have shown, for example, that even with identical resumes men are more positively evaluated as scientists relative to women by job search committees (Moss-Racusin et al 2012), that women with equivalent mathematical abilities to men nonetheless feel less confident in their own abilities (Ellis et al 2016), that women are less likely to receive strong reference letters from supervisors (Dutt et al 2016), and that common representations of science to children prominently portray men as scientists whilst women occupy other roles (Kerkhoven et al 2016). In geoscience, researchers have explored how fieldwork has been framed by heroic narratives emphasizing danger, strength, and masculine prowess, which has the effect of making women and others feel lacking or not welcome (Bracken and Mawdsley 2004;Carey et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Well-known issues such as familial obligation and childbirth have been identified as constraints on women's participation in science, but increasingly research is revealing the subtle and invisible ways in which scientific cultures privilege certain perspectives, bodies, and backgrounds and devalue others (Jarreau 2016;Skibba 2016;Cheryan et al 2017;Nelson 2017;Rosen 2017). Studies have shown, for example, that even with identical resumes men are more positively evaluated as scientists relative to women by job search committees (Moss-Racusin et al 2012), that women with equivalent mathematical abilities to men nonetheless feel less confident in their own abilities (Ellis et al 2016), that women are less likely to receive strong reference letters from supervisors (Dutt et al 2016), and that common representations of science to children prominently portray men as scientists whilst women occupy other roles (Kerkhoven et al 2016). In geoscience, researchers have explored how fieldwork has been framed by heroic narratives emphasizing danger, strength, and masculine prowess, which has the effect of making women and others feel lacking or not welcome (Bracken and Mawdsley 2004;Carey et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Differences were measured between the locations and sizes of the segmented regions. Local Consistency Error (LCE) (Kerkhoven et al ., ) was used to quantify the degree to which image segmentations were consistent with the ground truth. LCE can be represented as: LCES,R,pi=1Nfalse∑iminES,R,pi,OR,S,pi…”
Section: Methodsmentioning
confidence: 99%
“…Even though scientific argumentation is conducted via written and spoken language, visual representations can improve the clarity and communicability of evidence‐based arguments (Spiegelhalter, Pearson, & Short, ). However, the role of visual representations in scientific argumentation remains poorly understood (Kerkhoven, Russo, Land‐Zandstra, Saxena & Rodenburg, ), mainly because most research has examined students' conceptual understandings of images instead of their use of images as tools in epistemic practices like scientific argumentation (Evagorou & Erduran, ). Moreover, most studies that have investigated the use of images in science learning have manually and qualitatively characterized small samples of images (eg, Spiegelhalter, Pearson, & Short, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several gender-biased factors were identified in classes, which may facilitate stereotype formation [33]. These factors include the teaching and assessment methods a teacher chooses, which meet more or less the preferences of a certain sex category [34].…”
Section: Causes For Stereotype Formationmentioning
confidence: 99%
“…These factors include the teaching and assessment methods a teacher chooses, which meet more or less the preferences of a certain sex category [34]. In addition, the teachers' attitude to science and their function as a role model can be gender-biased, and the same applies for the selected contexts of a teaching content (e.g., technical vs. health-oriented contexts [35]), and also for the type of language and visuals (e.g., portraying mainly male scientists [36]) being used [33]. Teachers' gender-biased behaviors, however, can also be caused by the students themselves who trigger certain teacher reactions by their behavior.…”
Section: Causes For Stereotype Formationmentioning
confidence: 99%